Finance and Development, September 2016. (Finance and Development; Finance and Development ;, 2016)
This issue of Finance and Development focuses on how technology is driving growth. The issue looks at 'transmission channels.' As with drive-through tellers, ever-more-powerful technology allows us to streamline, replacing less efficient practices (the drive-through teller) with more efficient ones (smartphone deposits). Other articles in this issue cover package chronicle technology's power to transform: Sanjiv Ranjan Das examines big data's influence on economics and finance; Aditya Narain documents the rise of a new breed of hybrid financial technology-fintech-firms; and Sharmini Coorey touts distance learning for better policymaking. The issue also examines the impact of remittances on monetary policy, de-dollarization in Peru, and the efficacy of public-private partnerships, among other topics. It also presents profile of Nancy Birdsall, the former head of the Center for Global Development, who has dedicated her career to fighting poverty and inequality through compelling research.